Suprathermal electron dynamics and MHD instabilities in a tokamak. (October 2015) - Kamleitner, J; Coda, S; Decker, J; Graves, J P; the TCV team
Abstract The dynamics of suprathermal electrons in the presence of magnetohydrodynamics (MHD) activity and the excitation of MHD modes by suprathermal electrons are studied experimentally to improve the understanding of the interaction of fast particles with MHD instabilities in a tokamak. The study focuses on three different aspects of the internal kink mode with poloidal/toroidal mode number <?CDATA $m/n=1/1$ ?> <?MML m/n=1/1 ?><inline-graphic xlink:href="ark:/27927/pgj2j51dtr7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />: the sawtooth instability, electron fishbones and coupled bursts alternating with sawtooth crashes (CAS), all located where the safety factor <?CDATA $(q)$ ?> <?MML (q) ?><inline-graphic xlink:href="ark:/27927/pgj2j51dtjx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> profile approaches or takes the value <?CDATA $q=1$ ?> <?MML q=1 ?><inline-graphic xlink:href="ark:/27927/pgj2j51dtm1" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />. New quantitative results on suprathermal electron transport and an investigation of electron acceleration during sawtooth crashes are followed by the characterization of initial electron fishbone observations on the Tokamak à configuration variable (TCV). Finally, <?CDATA $m/n=1/1$ ?> <?MML m/n=1/1 ?><inline-graphic xlink:href="ark:/27927/pgj2j51dtdq" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> bursts associated with the sawtooth cycle, coupled to a persisting <?CDATA $m/n=2/1$ ?> <?MML m/n=2/1 ?><inline-graphic xlink:href="ark:/27927/pgj2j51dtgt" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> mode and alternating with sawtooth crashes, are discussed, in particular in view of the fast electron dynamics and their role in confinement degradation and mode excitation.